دراسة الشقوق حول منطقة بحيرة سد16 تشرين في/حوض نهر الكبير الشمالي/ (Latakia University Journal -Basic Sciences Series, 2017)
بينت الدراسة الإحصائية للشقوق في منطقة بحيرة 16 تشرين في حوض نهر الكبير الشمالي وجود عدة مجموعات رئيسة للشقوق ذات اتجاهات NE-SWإلىNNE-SSW، و NW-SE، و E-W.أظهرت المجموعة NE-SW توافقاً مع بنيات الصدوع من نفس الاتجاه وهي صدوع عادية وعكسية، تتوزع جغرافياً في نطاق صدع اللاذقية كلس، وتبدي أيضاً توافقاً مع محاور الطيات من نفس الاتجاه وبذلك تفسر على أنها شقوق طولية في هذه الطيات. كما أظهرت المجموعة NW-SE توافقاً مع بنيات الصدوع من نفس الاتجاه وهي صدوع إزاحية جانبية يمينية ويسارية تنتشر على كامل منطقة الدراسة وقد تشكل جملاً قصية (قطرية) في طيات ذات محاور NE-SW.كما أظهرت المجموعةE-Wتوافقاً مع بنيات الصدوع العادية.The statistical Study of Jointsarround 16 Tishreen lake dame region in ALKabir ALShimali river basin showed the presence of several main groups of Joints with directions NE-SW _ NNE-SSW, NW-SE, E-W. - Group NE-SW: showed correspond to with the fault structures of same directions which are normal and reversal faults and distributing geographically 1n Lattakia Kallas fault zone. Also it showes correspond to with the axis of folds of same direction, thus explained as longitudinal joints within these folds- Group NW-SE: showed correspond to with faults structures of same direction. which are left and right lateral strike slip faults, Spread over the entire study area. and it may(diagonal)shear group within the folds of NE-SW axes.- Group E-W:correspond to with normal faults structures.